The Effect of Being Faithful, Condom Use, no Drug Behavior on the Incidence of Sexually Transmitted Infections (STIs) in Unmarried Men Who Have Sex with Men (MSM) in Indonesia - Fatiah, Mona Safitri; Purba, Rispah; Molle, Genoveva Chatleen Compehage; Bela, Sarni Rante Allo (Unnes Journal of Public Health, 2025)
Background: “BCD” habits can help homosexual people and men who have sexwith men (MSM) prevent the transmission of sexually transmitted infections (STIs)and safeguard their partners. Objective: The purpose of this study was to investigate how BCD behaviour affects the prevalence of STIs among Indonesian MSM.Methods: a cross-sectional study was conducted in 24 provinces in Indonesia fromApril to May 2023. The study population comprised MSM who had ever engaged insexual intercourse, either occasionally, once, or frequently, totaling 6,000 individuals. A sample of 3,515 participants was selected using the Respondent Driven Sampling (RDS) method. Integrated Biological and Behavior Survey (STBP) 2018-2019data was utilized. The data was analyzed using multivariate analyses with STATA14 software. Results: after controlling for the variables of pieces of information exposure and vaginal intercourse, the following behaviors were found to have a significant influence of the occurrence of STIs among MSM (p-value:0.050; AOR:1,62with 95% CI:0.96-2.73), condom use (p-value:0.050; AOR:0.37 with 95% CI:0.14-1.00), no drug use (p-value:0.040; AOR:1,67 with 95% CI:1.02-2.75). Conclusion:promoting faithful behavior towards a steady partner, consistent condom use duringsexual activity, and refraining from injections and drug use can effectively reducethe transmission of STIs among MSM.